The transcription factor zinc fingers and homeoboxes 2 alleviates NASH by transcriptional activation of phosphatase and tensin homolog. Issue 4 (16th February 2022) - Zhao, Yichao; Gao, Lingchen; Jiang, Chenglin; Chen, Jianqing; Qin, Zihan; Zhong, Fangyuan; Yan, Yang; Tong, Renyang; Zhou, Meng; Yuan, Ancai; Pu, Jun
Abstract: Background and Aims: NASH, which is a common clinical condition predisposing to advanced liver diseases, has become a worldwide epidemic. A large and growing unmet therapeutic need for this condition reflects incomplete understanding of its pathogenesis. In the current study, we identified a transcription factor, zinc fingers and homeoboxes 2 (ZHX2), in hepatocytes as a protective factor against steatohepatitis. Approach and Results: We found that hepatic ZHX2 was significantly suppressed in NASH models and steatotic hepatic cells. Hepatocyte‐specific ablation of ZHX2 exacerbated NASH‐related phenotypes in mice, including lipid accumulation, enhanced inflammation, and hepatic fibrosis. Conversely, hepatocyte‐specific overexpression of ZHX2 significantly alleviated the progression of NASH in an experimental setting. Integrated analysis of transcriptomic profiling and chromatin immunoprecipitation sequencing data demonstrated that the phosphatase and tensin homolog (PTEN) was a target gene of ZHX2 in hepatocyte. ZHX2 bound to the promoter of PTEN gene and subsequently promoted the transcription of PTEN, which mediated the beneficial role of ZHX2 against NASH. Conclusions: The current findings demonstrate a protective role of ZHX2 against NASH progression by transcriptionally activating PTEN. These findings shed light on the therapeutic potential of targeting ZHX2 for treating NASH and related metabolic disorders.